Kinetics and Mechanism of Hydrolysis of Salicylidene-2- amino-1,3-pyrimidine Schiff Base in the Absence and Presence of Some Transition Metals - Gabr, A.A. (Asian Journal of Chemistry, 2010)
The hydrolysis of salicylidene-2-amino-1,3-pyrimidine Schiff base is studied kinetically in a series of universal buffer (2.37–11.40) containing 0.2 mole fraction of ethanol at 30ºC. Also, the effect of some transition metal ions (Cd(II), Mn(II), Fe(II), Co(II) and Ni(II)) on the hydrolysis rate of the Schiff base has been studied and discussed.